Muralart as a component of the cultural space of the city - A. O. Batenko (Ukrainian Cultural Studies, 2020)
The aim of the article is to define the role of mural art as a part of street art in the context of the cultural urban space. Identification of mural art in cities, its transformation depending on the place of creation and changes in the perception of the viewer requires needs research that is more detailed. А lot of people do not distinguish between concepts in street art; do not understand the artistic value of murals. Therefore, it is useful to show all functions, which murals can have. The quantity and quality of murals in the urban space affects its reputation, culture, development trends. That is, murals can both spoil urban visions and aestheticize them. Murals often engine enrichment of human consciousness, because artists raise important social issues, motivate the viewer to think. They try to turn the city into a large gallery, to influence people who involuntarily become spectators and connoisseurs of street art. It is also appropriate to explore the trends of Ukrainian muralism in the urban space. After all, street art has become very popular in Ukraine, as evidenced we can see various thematic festivals and competitions. The research methodology involves an interdisciplinary approach, analysis of scientific works of cultural and art history, review of thematic media and creative work of street artists to determine the characteristics and purposes of their activities. The works of modern Ukrainian researchers who study the issues of the cultural space of the city, mural art and street art in general are involved. The scientific novelty lies in the study of the influence of mural art on personal perception on drawing attention to socio-political problems in the urban context. On the example of the analysis of works of world street artists the tendency to social and educational function of murals, instead of simply aesthetic, is traced. The practical significance of the study is to emphasize that murals have artistic value, a unique semantic message, and are not just a means of aestheticization. The article can be useful for specialists in culturology, history, art history, architecture and for artists.